Analisis Kinerja Petugas Farmasi Pelayanan Obat Pasien Rawat Jalan Di RSUD dr.R.Soedjati Soemodiardjo Purwodadi - Grobogan - Christine Diah Wahyuningsih; Susilo Endrawanti (FEB UNTAG Semarang, 2017)
With the rising status of the community's economy, ease of communication and increasing knowledge about health causes people demand better quality health care, both in terms of attitude and behavior of officers. In accordance with Undang-Undang No. 77 |Tahun 2015 Tentang Pedoman Organisasi Rumah Sakit (Guidelines for the Organization's Hospital), the hospital must perform some functions which aims to realize a hospital organization that is effective, efficient, and accountable in order to achieve the vision and mission of the hospital in accordance with the Good Corporate Governance and Good Clinical Governance. In connection with the above description, researchers interested in conducting research titled